Development of a sulfonic gemini zwitterionic viscoelastic surfactant with high salt tolerance for seawater-based clean fracturing fluid. (2nd November 2019) - Zhang, Wenlong; Mao, Jincheng; Yang, Xiaojiang; Zhang, Heng; Zhao, Jinzhou; Tian, Jizhen; Lin, Chong; Mao, Jinhua
Highlights: A Gemini zwitterionic viscoelastic surfactant (VES-S) was synthesized, and the special molecule structure imparts high salt tolerance to VES-S. The mechanism of salt tolerance of VES-S is explained. Seawater based fracturing fluids prepared by VES-S perform well in laboratory evaluation. Abstract: In this study, a gemini zwitterionic viscoelastic surfactant with a sulfonic group, named VES-S, was synthesized. The surface activity properties of VES-S were found to show an ultra-low sensitivity to the salt concentration compared to those of cationic gemini surfactants, meaning that the packing parameter of VES-S varies little with increasing salinity. Through laboratory measurements, it was found that the addition of salt can enhance the viscoelasticity of the VES-S solution by tightening the net-work structure even at a high NaCl concentration (8 wt%), which indicated that VES-S was a viscoelastic surfactant with high salt tolerance. A series of laboratory evaluations showed that the clean fracturing fluids prepared by VES-S and simulated seawaters fulfilled the requirements for hydraulic fracturing operations, which proved that VES-S was an excellent and reliable viscoelastic surfactant with a high salt tolerance that can be used to prepare seawater-based clean fracturing fluids.